Comparison of COVID-19 home-testers vs. laboratory-testers in New York State (excluding New York City), November 2021 to April 2022 - Dorabawila, Vajeera; Barnes, Virgile; Ramesh, Nirmala; Hoen, Rebecca; Sommer, Jamie; Robbins, Amy; Backenson, Byron; Lutterloh, Emily; Hoefer, Dina; Rosenberg, Eli (Frontiers in Public Health, 2023)
Background: Home testing is not represented in publicly reported COVID-19 metrics, and use of home-testing is increasing. As the epidemic and its tracking evolves, it is critical to understand who the excluded home tested persons are relative to those in reported metrics. Methods: Five New York State databases were linked to understand trends in home-tested COVID-19 cases compared with laboratory confirmed cases from November 2021 to April 2022. Frequency distributions and multivariate logistic regression adjusted odds ratios (aOR) and 95% Confidence Intervals (CI) were used to compare characteristics of home-tested to laboratory-tested persons. Results: Of 592,227 confirmed COVID-19 cases 71,531 (12%) had a home-test-only, 515,001 (87%) had a laboratory-test-only and 5,695 (1%) had both a home-test and laboratory-test during this period. Home-tested cases as percent of confirmed COVID-19 cases increased from 1% in November 2021 to 22% in April 2022. Children aged 5-11 years with 3.74 aOR (95% CI: 3.53, 3.96) and adolescents aged 12-17 years with 3.24 aOR (95% CI: 3.07, 3.43) were more likely to have home-test-only relative to adults 65 and above. Boosted (aOR 1.87, 95% CI: 1.82, 1.93), in K-12 school settings (aOR 2.33, 95% CI: 2.27, 2.40) or those possibly infected by a household member (aOR 1.17, 95% CI: 1.13, 1.22) were more likely to report home-test-only compared to laboratory-test-only. Persons hospitalized (aOR 0.04, 95% CI: 0.03, 0.06), with underlying conditions (aOR 0.85, 95% CI: 0.83, 0.87), pregnant (aOR 0.76, 95% CI: 0.66, 0.86), Hispanic (aOR 0.50: 95% CI: 0.48, 0.53), Asian (aOR 0.31, 95% CI: 0.28, 0.34) or Black (aOR 0.45, 95% CI: 0.42, 047) were less likely to utilize home-test-only compared to laboratory-test-only. Conclusion: Persons using home-test-only as a proportion of confirmed COVID-19 cases continue to increase. Home-test-only cases are less likely be hospitalized and are those with lower potential for severe disease measured by age, vaccination status, and underlying conditions. Thus, those with severe disease and potential for severe disease are represented official metrics. Racial and ethnic differences in persons reporting home-tests versus laboratory-tests exist.